2015
DOI: 10.7763/jocet.2015.v3.195
|View full text |Cite
|
Sign up to set email alerts
|

Solubility of Organics in Triethylene Glycol: Phase Equilibrium Modelling Using the Dortmund and LYNGBY Modified UNIFAC Models

Abstract: Abstract-This work is an attempt to predict the solubility of 60 volatile organic compounds (VOCs) in triethylene glycol aimed at thermodynamically testing the suitability of this solvent as an absorbent for the selected organics. The VOC main groups studied were alkanes, alkenes, alkynes, aldehydes, carboxylic acids and alcohols. The Modified UNIFAC Dortmund and Lyngby models were to study the required phase equilibrium as a function of temperature and composition. Triethylene glycol was found to be suitable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The outcomes of molecular dynamic computations have demonstrated that UNIQUAC frequently exhibits a tendency to excessively rectify deviations associated with random mixing due to the significant magnitudes observed in the arguments of the Boltzmann factors. Consequently, UNIQUAC tends to fall short in some cases in terms of precision when utilized for liquid–liquid equilibrium (LLE) calculations, as compared to the NRTL model . In comparison to NRTL, UNIQUAC exhibits greater mathematical complexity; however, it offers three distinct advantages when employed in thermodynamic modeling: First, the UNIQUAC model encompasses solely two adjustable parameters per binary, as opposed to the three parameters required by NRTL.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The outcomes of molecular dynamic computations have demonstrated that UNIQUAC frequently exhibits a tendency to excessively rectify deviations associated with random mixing due to the significant magnitudes observed in the arguments of the Boltzmann factors. Consequently, UNIQUAC tends to fall short in some cases in terms of precision when utilized for liquid–liquid equilibrium (LLE) calculations, as compared to the NRTL model . In comparison to NRTL, UNIQUAC exhibits greater mathematical complexity; however, it offers three distinct advantages when employed in thermodynamic modeling: First, the UNIQUAC model encompasses solely two adjustable parameters per binary, as opposed to the three parameters required by NRTL.…”
Section: Resultsmentioning
confidence: 99%
“…Remarkably, its applicability extends to lactate compounds, including butyl lactate, , while also including partially miscible systems as well as completely miscible mixtures . This versatile model has thus garnered recognition and utility in various complex scenarios, making it a useful tool for comprehensive research in the realm of intermolecular interactions and phase equilibria analysis …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations